2008
DOI: 10.1038/gt.2008.37
|View full text |Cite
|
Sign up to set email alerts
|

Gene-modified bone marrow cell therapy for prostate cancer

Abstract: There is a critical need to develop new and effective cancer therapies that target bone, the primary metastatic site for prostate cancer and other malignancies. Among the various therapeutic approaches being considered for this application, gene-modified cell-based therapies may have specific advantages. Gene-modified cell therapy uses gene transfer and cell-based technologies in a complementary fashion to chaperone appropriate gene expression cassettes to active sites of tumor growth. In this paper, we briefl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 116 publications
(133 reference statements)
0
4
0
Order By: Relevance
“…Unfortunately, very little information is available in the literature regarding bone marrow cell therapy that targets metastatic prostate cancer. Wang and Thompson, 2008 summarized the importance of developing gene-modified bone marrow cell therapy for advanced prostate cancer [ 120 ]. A previous study has demonstrated that IL-12-gene-modified bone marrow cell therapy suppressed the development of experimental prostate cancer metastasis in a preclinical mouse model [ 121 ].…”
Section: Bone Marrow Cell Therapy For Metastatic Prostate Cancermentioning
confidence: 99%
“…Unfortunately, very little information is available in the literature regarding bone marrow cell therapy that targets metastatic prostate cancer. Wang and Thompson, 2008 summarized the importance of developing gene-modified bone marrow cell therapy for advanced prostate cancer [ 120 ]. A previous study has demonstrated that IL-12-gene-modified bone marrow cell therapy suppressed the development of experimental prostate cancer metastasis in a preclinical mouse model [ 121 ].…”
Section: Bone Marrow Cell Therapy For Metastatic Prostate Cancermentioning
confidence: 99%
“…13,14 Alternative approaches have been tested, including gene-modified cell-therapy approaches that focus on the delivery of therapeutic genes to the PCa, such as interleukin 12 (IL-12) gene-modified macrophage therapy. 15 The results of that study demonstrated suppression of tumor growth and spontaneous lung metastasis, induction of systemic antitumor immune response, and prolongation of survival in mouse orthotopic models of metastatic PCa.…”
Section: Introductionmentioning
confidence: 99%
“…Almost one in six men will be diagnosed with prostate cancer during their lifetime. Although the second leading cause of death from cancer, prostate cancer is a relatively slow-growing malignancy that may be amenable to the applications of cellular therapy [17]. CEPs are increased in the peripheral blood of prostate cancer patients [18], and TAMs also play a crucial role in the development and metastasis of prostate tumors [9].…”
Section: Introductionmentioning
confidence: 99%